Impacto del COVID 19 en las actividades económicas-financieras de las Cooperativas de Ahorro y Crédito del Segmento Uno - Macias Ostaiza, Darhil E. (2023)
The general objective of the research was to determine the impact of COVID-19 on the economic-financial activities of segment one savings and credit cooperatives to identify the level of variation with respect to historical data. The sample was for convenience and was made up of 25 Cooperatives from segment one of Ecuador. The type of research was cross-sectional, bibliographic, quantitative, qualitative and exploratory. The methods were descriptive and analytical. The techniques financial analysis, vertical analysis, horizontal analysis, financial indicators, literature review and forecasting techniques. The tools were the PEARLS method. The data collection was structured in three phases: in the first, the horizontal and vertical analysis of the financial statements of the segment one savings and loan cooperatives was carried out; in the second, the financial indicators established by the PEARLS methodology were quantified to identify the variations of the last four years in the savings and credit cooperatives of segment one and in the third, the impact of COVID-19 on the behavior of the financial economic data of the cooperatives under study. It is possible to conclude that there is evidence of a decrease in assets, placement of credits and equity. The PEARLS method facilitated the elaboration of the quantification of the financial indicators for the analysis, scientifically establishing the level of incidence of the Covid-2019 pandemic on the aforementioned sector. Finally, the analysis and interpretation of the pre-determined financial indicators allowed us to verify the reduction of the corporate development indicators and the increase of the loss indicators.